2015
DOI: 10.1007/978-3-319-12805-4_8
|View full text |Cite
|
Sign up to set email alerts
|

The Response of German Establishments to the 2008–2009 Economic Crisis

Abstract: This series is designed to make available to a wider readership selected labour market, social policy and migration studies prepared for use within the OECD. Authorship is usually collective, but principal writers are named. The papers are generally available only in their original language -English or French -with a summary in the other.Comment on the series is welcome, and should be sent to the Directorate for Employment, Labour and Social Affairs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 21 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…Bellmann et al, 2015;Boeri and Bruecker, 2011) that have focused on this variable as a conditioning factor for the overall employment response. In our framework, the pre-crisis TAW share is a predetermined variable, while STW use, which is measured in the (post-)crisis years 2009 and 2010, is fully endogenous and measures a reaction to the crisis.…”
Section: Empirical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Bellmann et al, 2015;Boeri and Bruecker, 2011) that have focused on this variable as a conditioning factor for the overall employment response. In our framework, the pre-crisis TAW share is a predetermined variable, while STW use, which is measured in the (post-)crisis years 2009 and 2010, is fully endogenous and measures a reaction to the crisis.…”
Section: Empirical Strategymentioning
confidence: 99%
“…the German labour market performance in the Great Recession (Bellmann et al, 2015;Burda and Hunt, 2011;Boeri and Bruecker, 2011;Bohachova et al, 2011;Möller, 2010)). 2 These studies, however, do not focus on the role of temporary agency employment as a potentially stabilizing factor.…”
Section: Introductionmentioning
confidence: 99%
“…4 In yet other countries, employers bear no short-time work cost at all. 5 Our results stress that systems where employers contribute little to short-time work induce …rms facing strong seasonal revenue ‡uctuations to make recurrent use of short-time work, which reduces aggregate production. Given that, it is important to limit the recurrent use of short-time work.…”
Section: Brunet Et Al (2009)mentioning
confidence: 67%
“…This result approximates the empirical evidence of the micro literature based on firm‐level data which in general has not found any significant net effects of STW on employment (Bellmann et al . ; Calavrezo et al . ), departing from the large positive impacts found by others (Boeri and Bruecker ).…”
Section: Discussionmentioning
confidence: 94%
“…On the micro side, Boeri and Bruecker () and Bellmann et al . () use an instrument based on the experience of firms with STW before the crisis. In general, macro studies have found short‐time positive impacts of STW on employment during the 2008–2009 recession (although deadweight costs seem to be sizable as well, especially in the medium run), whereas empirical evidence from micro studies which control for STW endogeneity are not so clear‐cut, showing either small positive effects or no effect at all…”
Section: Introductionmentioning
confidence: 99%